The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1096/fj.202000524rr
|View full text |Cite
|
Sign up to set email alerts
|

The displacement of frataxin from the mitochondrial cristae correlates with abnormal respiratory supercomplexes formation and bioenergetic defects in cells of Friedreich ataxia patients

Abstract: Friedreich ataxia (FRDA) is a neurodegenerative disease resulting from a severe decrease of frataxin (FXN). Most patients carry a GAA repeat expansion in both alleles of the FXN gene, whereas a small fraction of them are compound heterozygous for the expansion and a point mutation in the other allele. FXN is involved in the mitochondrial biogenesis of the FeS‐clusters. Distinctive feature of FRDA patient cells is an impaired cellular respiration, likely due to a deficit of key redox cofactors working as electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…We cannot exclude the possibility that FXN G130V (and Fxn G127V) carries out distinct functions or performs its activity with different kinetics, thus affecting clinical presentations or phenotypes. It is interesting to speculate that FXN G130V (Fxn G127V) is a less stable but functionally “better” frataxin that can more efficiently compensate the overall frataxin deficit in FRDA G130V patients, which is also a dramatic loss compared to homozygous repeat expansion patients ( Clark et al, 2017 ; Doni et al, 2021 ; Lazaropoulos et al, 2015 ), and Fxn G127V/G127V animals, thus allowing the mice to survive expressing a very low amount of frataxin.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that FXN G130V (and Fxn G127V) carries out distinct functions or performs its activity with different kinetics, thus affecting clinical presentations or phenotypes. It is interesting to speculate that FXN G130V (Fxn G127V) is a less stable but functionally “better” frataxin that can more efficiently compensate the overall frataxin deficit in FRDA G130V patients, which is also a dramatic loss compared to homozygous repeat expansion patients ( Clark et al, 2017 ; Doni et al, 2021 ; Lazaropoulos et al, 2015 ), and Fxn G127V/G127V animals, thus allowing the mice to survive expressing a very low amount of frataxin.…”
Section: Discussionmentioning
confidence: 99%
“…Both SOD2 and FXN [ 28 ] are able to regulate the detoxifying enzymatic mechanisms and inhibit ROS production, and they might act synergistically, since the two proteins are located in the same mitochondrial compartment. Recently, it has been demonstrated that FXN is enriched in the mitochondrial cristae, and its involvement in stabilizing the organization of respiratory chain has been hypothesized based on functional and biochemical analyses [ 50 ]. Interestingly, recent cryo-EM studies showed that SOD2 is associated with respiratory supercomplexes in both mycobacteria [ 51 ] and Caenorhabditis elegans [ 52 ], an association that can provide local protection against ROS damage.…”
Section: Discussionmentioning
confidence: 99%
“…Frataxin is a mitochondrial protein involved in cellular iron homeostasis and functions as a chaperone during iron-sulfur cluster and heme synthesis by incorporating iron to their precursors ( Yoon and Cowan, 2004 ). The deficiency of frataxin has been associated with reduced activity of mitochondrial respiratory chain complexes, lower ATP production and decreased mitochondrial content, as well as iron accumulation and oxidative stress ( Lodi et al, 1999 ; Bradley et al, 2000 ; Schulz et al, 2000 ; Jasoliya et al, 2017 ; Lin et al, 2017 ; Doni et al, 2021 ). Even though it was not previously classified ( Saudubray and Garcia-Cazorla, 2018a ), since the deficient protein leads to mitochondrial iron overload and consequent defective energy supply ( Yoon and Cowan, 2004 ), FRDA might be categorized either in the group of small molecule defects or energy-related disorders.…”
Section: Nrf2 Signaling Disruption In Inherited Metabolic Disordersmentioning
confidence: 99%